2013
DOI: 10.1103/physrevb.87.104113
|View full text |Cite
|
Sign up to set email alerts
|

Local atomic structure deviation from average structure of Na0.5Bi0.5TiO3

Abstract: The crystal structure of sodium bismuth titanate and related compounds is of great interest, as these may form part of a new generation of ferroelectric materials used in a multitude of piezoelectric applications. This work examines the short and long range structure of sodium bismuth titanate in different states of synthesis using X-ray and neutron pair distribution function studies. The average structure of NBT was modeled using the monoclinic Cc space group through a combined structural refinement of X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 38 publications
12
73
0
1
Order By: Relevance
“…[18][19][20][21][22][23][24][25] Our work shows there are two types of NBT based on the level of nonstoichiometry (resistive stoichiometric NBT and conducting Bi-deficient NBT). It's not clear whether the NBT samples used in the structural studies reported in the literature are resistive or conducting and whether or not these two electrically distinct materials have the same crystal structure.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…[18][19][20][21][22][23][24][25] Our work shows there are two types of NBT based on the level of nonstoichiometry (resistive stoichiometric NBT and conducting Bi-deficient NBT). It's not clear whether the NBT samples used in the structural studies reported in the literature are resistive or conducting and whether or not these two electrically distinct materials have the same crystal structure.…”
Section: Discussionmentioning
confidence: 78%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] NBT has a complex crystal structure. [18][19][20][21][22][23][24][25] Early neutron powder diffraction studies proposed NBT to exhibit a rhombohedral (space group R3c) structure at room temperature (RT). 18 Recent high resolution synchrotron powder x-ray diffraction data suggest a monoclinic structure with space group Cc is a better fit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The random distribution of Bi and Na on the A site leads to the averaged crystal structure in space group Cc [19] while the structure of BNT for the DFT calculations should have a lower symmetry due to an arrangement of Bi and Na [55]. We selected the monoclinic supercell in space group Pc (BiNaTi 2 O 6 , Z = 4, see Figure 1b), in which the structural feature in the Cc cell can be taken into account.…”
Section: Methods Of Dft Calculationsmentioning
confidence: 99%
“…The considerable deviation of the short-and intermediaterange order in pure NBT from the long-range order of the average structure was demonstrated by recent x-ray absorption spectroscopy (XAS) [12] and neutron total elastic scattering (TES) [13,14]. Both methods revealed that (i) the off-centering of B-site Ti 4+ cations is only slightly influenced by temperatures and persists in the high-temperature paraelectric phase at least up to 870 K, and (ii) the off-centering of A-site Bi 3+ is considerably larger and less dispersed than that of A-site Na + cations.…”
Section: Introductionmentioning
confidence: 99%